PERAN HAFALAN TAHFIDZ HADITS MAUDZU'I SANTRI PONDOK PESANTREN ISLAMIC CENTER eLKISI PADA KAFILAH DAKWAH RAMADHAN DI DESA MOJOREJO KECAMATAN PUNGGING KABUPATEN MOJOKERTO - Umam, Hisbul; Shafwan, Muhammad Hambal (Jurnal Staika: Jurnal Penelitian dan Pendidikan, 2025)
This research aims to discuss the role of memorizing the tahfidz hadith of Maudzu'i students at the eLKISI Islamic Center Islamic Boarding School in the Ramadhan preaching caravan in Mojorejo village, Pungging sub-district, Mojokerto district." This research is qualitative research with a case study approach, which means this research was conducted in a natural context to understand the phenomena that occur. The methods used include various techniques to carry out in-depth interpretation of the phenomenon. The results of this research explain that the memorization of tahfidz hadith by students at the eLKISI Islamic Center Islamic Boarding School has an important role in the Ramadhan Da'wah Caravan in the Village. This memorization helps students convey Islamic messages and teachings more clearly and authentically, provide accurate explanations and interpretations, increase courage and self-confidence, and strengthen the diversity of the community in understanding and practicing Islamic teachings. Education to memorize the tahfidz hadith of Maudhu'i by combining classical classroom learning and halaqoh learning in the mosque has a very positive and satisfying impact in forming a mental readiness to preach in the community or in remote areas.